Global Liquidity through the Lens of Monetary Aggregates - Chung, Kyuil; Lee, Jong-Eun.; Loukoianova, Elena; Park, Hail. (Washington, D.C. : International Monetary Fund, 2014)
This paper examines how the financial activities of non-financial corporates (NFCs) in international markets potentially affects domestic monetary aggregates and financial conditions. Monetary aggregates reflect, in part, the activities of NFCs, who channel capital market financing into the domestic banking system, thereby influencing funding conditions and credit availability. Periods of capital inflows are also those when the domestic currency is appreciating, and such periods of rapid exchange rate appreciation coincide with increases in the central bank's foreign exchange reserves, increasing the stock of narrow money. The paper examines economic significance of cross-country panel data on monetary aggregates and other measures of non-core bank liabilities. Non-core liabilities that reflect the activities of NFCs reflect broad credit conditions and predict global trade and growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet